The Thirsty Traveler and Luck-Free Moral Luck - Kahn, Samuel (Problemos, 2024)
This article is divided into three sections. In the first and second, I examine Sartorio’s account of the causal structure of the famous Thirsty Traveler thought experiment. I argue that this account does not withstand critical scrutiny. In the third, I turn to a novel kind of moral luck that Sartorio uses the Thirsty Traveler to expose. I expand the scope of my argument to look also at other recently proposed categories of moral luck. I argue that these proposals are overhasty
Keywords: thirsty traveler; moral luck; moral responsibility; causal responsibility; Sartorio